A review on modern imaging techniques for characterization of nanoporous unconventional reservoirs: Challenges and prospects. (November 2021) - Bera, Achinta; Shah, Subhash
Abstract: Characterization and modeling of unconventional reservoirs are quite challenging as the fluid flow through nanoporous media is not well-understood due to complexity of such reservoirs. Unlike conventional reservoirs, there is no migration of gas due to the ultra-low permeability of unconventional reservoir rock. Hence, the gas can be accumulated or trapped in nanopore spaces, natural fractures, or can be adsorbed onto the bulk surface of organic materials of unconventional reservoir rock. In this paper, discussion of different unconventional reservoirs and various methods and tools used for their characterization are discussed. Modern imaging techniques such as micro and nano computerized tomography (micro-CT and nano-CT) scans, scanning electron microscope (SEM), field emission scanning electron microscope (FESEM), small-angle neutron scattering (SANS), ultra-small-angle neutron scattering (USANS), atomic force microscope (AFM), and neutron magnetic resonance (NMR) have been available for understanding the difficulty of characterization methodologies due to the presence of complex nanopore system. A thorough discussion on the applications of aforementioned imaging techniques is deliberated. In addition, advantages and disadvantages of the imaging techniques along with economic analysis of using these instruments for unconventional reservoir characterization for a field development project are depicted. Finally, the challenges and prospects of unconventional reservoir characterization and modeling for the mitigation of energy demand are also discussed. Graphical abstract: Image 1 Highlights: Nanoporous unconventional reservoirs show the complex nature as permeability ranges from 0.1 to 0.5 mD. Imaging techniques like CT scan, AFM, SEM, FESEM, SANS, USANS, and MNR are very useful for pore network characterization. SEM/FESEM and CT scan techniques have major contribution in research for reservoir characterization rather than others. Each imaging technique has advantages and disadvantages in rock sample analysis. The initial cost of imaging technique is high and longer use can pay back to show economic feasibility in characterization.